A continuing legend: the Brookhart-type α-diimine nickel and palladium catalysts. Issue 19 (2nd May 2019) - Wang, Fuzhou; Chen, Changle
Abstract : Here we will summarize some of the recent advances in α-diimine ligand developments, as well as some new and challenging monomers that this class of catalysts can address through these ligand improvements. Abstract : The Brookhart-type α-diimine nickel and palladium catalysts are one of the most examined systems in the field of olefin polymerization. Even after more than twenty years of extensive research, they continue to attract a lot of attention. In addition to their ease of synthesis and structural versatility, the chain walking capability and great polar group tolerance represent some of their most fascinating features. Followed by some brief descriptions of the chain walking mechanism, this review summarizes some recent advances in α-diimine ligand modifications. Specifically, it is categorized into three aspects: modifications of N -aryl substituents, modifications of ligand backbone structures, and the utilization of dinucleating ligands. Influences of steric and electronic effects on catalytic properties are demonstrated. Some recent developments in copolymerizations of olefins with polar comonomers to produce functionalized polyolefin materials are also discussed.